Perancangan Website Sekolah Berbasis CMS Sekolahku di SDIT Al-Irsyad Dermayu (Current Research in Education: Conference Series Journal, 2023)
This research was conducted in order to fulfill the outcomes of the Industrial Practice Program of PSTI UPI Purwakarta Campus. Practical activities were carried out at the Integrated Islamic Elementary School (SDIT) Al-Irsyad Dermayu, Indramayu, West Java. Based on the preliminary study, there are problems that occur in the practice location, namely the lack of promotional media and dissemination of school information for stakeholders, especially the community. This is because the promotional media for SDIT Al-Irsyad Dermayu is limited, that is, it only has promotional media in the form of social media accounts and does not update information regularly. Thus, the researcher took the initiative to overcome these problems through the creation of a school website and providing special training for school admin employees to be able to manage the website in a sustainable manner. The method used in this research is applied research method. The implementation of the treatment was tested with the Technology Acceptance Model (TAM) research design to determine user perceptions of the website. The result of this activity is the SDIT Al-Irysad Dermayu website based on My School CMS which can display various school information for the wider community. The results of the Technology Acceptance Model (TAM) test obtained a value of 93.8% from a total of 16 respondents. Respondents stated that the school information website that was created could be a solution to the problem of promotion and news delivery at SDIT Al-Irsyad Dermayu, so that the functional system has been running well and according to user needs.